The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1177/1060028015591846
|View full text |Cite|
|
Sign up to set email alerts
|

Dosing of Target-Specific Oral Anticoagulants in Special Populations

Abstract: Pharmacokinetic and pharmacodynamic changes associated special populations may alter clinical decision with regard to drug selection and dosing. It is valuable to understand the rationale for labeled dosing recommendations in nonvalvular atrial fibrillation and venous thromboembolism treatment and prevention, particularly in patients that fall into special population groups. Furthermore, the use of TSOACs is likely to increase as clinicians gain experience with these agents and additional TSOACs and indication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Rivaroxaban's onset of action is 30 minutes, faster than the 36-72 hours for warfarin (which requires overlap with heparin therapy). Interactions of NOACs with other drugs are rare, with the exception of a few antibiotics and antifungals, which may be significant for patients with malignancy [ 26 ].…”
Section: Advantages Of Noacs For Vtementioning
confidence: 99%
“…Rivaroxaban's onset of action is 30 minutes, faster than the 36-72 hours for warfarin (which requires overlap with heparin therapy). Interactions of NOACs with other drugs are rare, with the exception of a few antibiotics and antifungals, which may be significant for patients with malignancy [ 26 ].…”
Section: Advantages Of Noacs For Vtementioning
confidence: 99%
“…The percentage of obese patients enrolled was small. In the subgroup studies, the efficacy and the safety of the NOACs in obese patients 53 were good, although the RE-COVER study showed a non-significant trend towards a higher incidence of VTE events in patients with BMI >30 kg/m 2 , 2 these data seem to be in contrast with the results of the Randomized Evaluation of Long-term anticoagulant TherapY study (RE-LY) 56 …”
Section: Disputes About Using Non-vitamin K Dependent New Oral Anticomentioning
confidence: 97%
“…However, the inclusion criteria showed some differences among trials 3 , 7 , 10 , 52 . Regarding chronic RF, due to the different pharmacokinetics of the molecules, that have a specific elimination, an increased incidence of VTE events and bleeding complications during anticoagulant therapy has been documented 53 . Patients with chronic RF have been excluded from the recruitment in the clinical trials evaluating the NOACs.…”
Section: Disputes About Using Non-vitamin K Dependent New Oral Anticomentioning
confidence: 99%
See 1 more Smart Citation
“…Dosing and treatment considerations of these agents have been reviewed previously. 79 The purpose of this article was to describe the novel pharmacology and mechanisms of action of the new oral anticoagulants as they relate to their use among solid organ transplant recipients. This will include discussion of dosing in patients with impaired renal and hepatic function, considerations for drug-drug interactions with immunosuppressive medications, and management of patients at the time of unplanned surgery.…”
Section: Introductionmentioning
confidence: 99%